Anti-inflammatory effectiveness of Cymbopogon citratus DC. Staff in Na CMC gel preparation - Indrawati, Teti; Hakim, Zainur Rahman; Rahayu, Renu; Djuhariah, Yayah St (Faculty of Pharmacy, Universitas Pancasila, 2025)
Cymbopogon citratus DC. Stapf contains saponins, tannins, and flavonoids. Traditionally, tea from lemongrass leaves is useful as an anti-inflammatory, anti-malarial, anti-mutagenic, anti-mycobacterial, antioxidant, hypoglycemic, and neurobehavioral. A study has been conducted to formulate an anti-inflammatory gel preparation from C. citratus extract. The study was conducted by macerated a C. citratus leafs using 70% ethanol, then evaporated in a rotary evaporator at a temperature of 40 ºC until viscouse extract obtained and evaluated. The anti-inflammatory gel was prepared using Na CMC 6%, with the concentration of C. citratus extract 6%, 8%, and 10%. The resulting gel preparation was evaluated for its physical and chemical properties and then tested for its anti-inflammatory effects using male mice (Mus musculus L.). Flavonoids, alkaloids, tannins, and saponins are found in this C. citratus extract. The characteristics of the C. citratus extract gel made were, brown and dark brown, had a distinctive C. citratus odor, semi-solid, and homogeneous, had a pH of 5.54–5.62, a viscosity value between 57000-73000 cP, had pseudoplastic flow properties, a specific gravity between 1.055-1.078 g/cm3, had an adhesiveness of 231-252 seconds, and a spreadability of 3490.11-3021.20 mm2. The gel contained 10% of C. citratus extract, indicating the highest anti-inflammatory effect, with a decrease in edema diameter of 67.79% in the legs of male mice.